Assessment of fluid neutral models for a detached ITER case. (August 2017) - Horsten, N.; Dekeyser, W.; Samaey, G.; Baelmans, M.
Highlights: Assessment of fluid neutral models by comparing the resulting plasma sources with the sources from a Monte Carlo simulation of the kinetic equation for a fixed background plasma. A single pressure-diffusion equation is sufficient for the prediction of the particle source, but not for the parallel momentum and ion energy source. A parallel momentum equation has to be added to also obtain accurate results for the momentum and ion energy source (within 30% of accuracy). The error is further reduced by adding a neutral energy equation (within 15% of accuracy). Abstract: We compare the plasma sources (particle, parallel momentum and ion energy) due to plasma-neutral interactions computed with different fluid neutral models with the sources from a Monte Carlo simulation of the kinetic neutral equation. This is done for a fixed background plasma, which is representative for an ITER detached case. We illustrate that the reaction data from the AMJUEL-HYDHEL databases can be incorporated in the fluid models. A pure pressure-diffusion equation gives already accurate results for the particle source, but it is inaccurate for the momentum and energy source. A parallel momentum equation has to be added to achieve predictions of the momentum and energy source within 30% of accuracy. Newly developed boundary conditions, based on the diffusion approximation for incident neutrals, show to be crucial for accurate results of the fluid models close to the divertor target. The slight overestimation of the momentum and energy sources can be further reduced by adding a separate neutral energy equation.